A Case Report of Intraductal Papillary-Mucinous Neoplasm of the Pancreas Showing Morphologic Transformation during Followup Periods. (15th October 2009) - Sanada, Yuichi; Osada, Shinji; Tanaka, Yoshihiro; Tokuyama, Yasuharu; Yoshida, Kazuhiro
Abstract : A 64-year-old man underwent MRCP for further examination of gallbladder stones and IPMN of branch-type (IPMN-Br) was pointed out. Yearly MRCP had revealed the gradual increase of the cystic components, marked dilation of the main pancreatic duct (MPD), and filling defects in the MPD. After follow-up for three years, he underwent pancreatoduodenectomy. Histologically, the dilated MPD and connecting dilated branch ducts were filled with nodular growth of tumor cells consisting of gastric-type adenoma with pyloric gland-like structures. In the MPD, a transition from gastric-type adenoma to intestinal-type carcinoma was observed. In addition, in a dilated branch duct, some components of intestinal-type carcinoma with marked arborizing structures were observed. A minimally invasion was observed around branch ducts. Immunohistochemistry revealed diffuse nuclear accumulation of PCNA and Ki67 in the tumor cells of branch dusts. Our observations suggest that the secondary infiltration to the MPD of IPMN-Br and IPMN-Br possesses malignant potential for microinvasion.